Prioritization of applicable drivers for green supply chain management implementation toward sustainability in Thailand. Issue 2 (4th March 2017) - Somsuk, Nisakorn; Laosirihongthong, Tritos
ABSTRACT: It is essential that the green supply chain management (GSCM) implementation is effectively supported by several strategic drivers for successful implementation and sustainability, especially for the 'green' start-ups with a sustainability-driven organizational strategy. This study aims to determine and prioritize the applicable drivers for GSCM implementation of sustainable development strategies in the electronics industry in Thailand. The applicable drivers and their priorities are obtained by applying the fuzzy group decision-making approaches including fuzzy Delphi and fuzzy Analytic Hierarchy Process, based on Thai experts' perspectives. In this study, three prominent organizational theories, resource-based view, relational view, and institutional theory, are needed to explain the drivers of sustainability and to develop a hierarchical model for prioritization of the drivers. Finally, based on the findings of this study, several recommendations are made that may help to improve the sustainable development in Thailand through more effective implementation of GSCM.